Tantangan Rumah Sakit dalam Proses Implementasi Kebijakan Kelas Rawat Inap Standar: Literatur Review - Mutiara Sitha Putri; Djazuly Chalidyanto (Universitas Airlangga, 2025)
Background: The government is committed to meeting the basic health needs of the Indonesian people through the National Health Insurance (JKN) Program ensuring access to health services without financial burdens. The implementation of the inpatient class system is considered suboptimal, so the government has implemented the Standard Inpatient Class (KRIS) policy to ensure equitable health services for all people in accordance with the principle of equity. This policy requires hospitals to meet 12 specified criteria no later than June 30, 2025. The process of preparing and implementing the policy presents various challenges, so further research is needed. Objectives: This study aims to identify the challenges faced by hospitals during in implementing the Standard Inpatient Class (KRIS) policy. Methods: A literature review was conducted using Google Scholar as the primary database, by analyzing nine articles that meet the inclusion and exclusion criteria. Results: The results of the study found that the main challenges for hospitals in the process of implementing the KRIS policy infrastructure that fails to meet the required criteria due to budget limitations, the absence of regulations on the health financing system and KRIS rates, the lack of health human resources, and limited understanding of KRIS. In addition, the uneven dissemination of policies to hospital staff and the community also becomes an obstacle in implementing the policy. Conclusion: The implementation of standard inpatient class policies presents challenges for hospitals. These challenges can be found both in the preparation process and during policy implementation. The results of the study found that the readiness of facilities and infrastructure, lack of budget, uncertainty in the health financing system, health human resources and policy dissemination are aspects that are challenges for hospitals. These challenges must be managed so that the objectives of policy implementation can be achieved.